FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA BALAI LATIHAN KERJA (BLK) SURAKARTA - Aris Tri Haryanto, Dodi Suhardiyono & (JI@P, 2017)
Dodi Suhardiyono, 2017. â factors Affecting the Performance ofSurakarta Training Officeâ. Graduate Program of PublicAdministration Slamet Riyadi University, Thesis, unpublished.This research aimed to describe factors affecting the performanceof Surakarta Training Office. This research used descriptivequalitative method. Interview as well as observation collecting datatechniques were employed to derive primary data. Documentstudy was employed for obtaining secondary data in the year of2014 up to 2016. Interactive data analysis as suggested by Milesand Huberman was used for anaylising the data.Productivity is one of the factors affecting the performance wasmeasured by mean of the ratio of training implementation, mean ofratio of number of training participant, ratio of graduated of trainingand the ratio of placement. Based on the indicator of responsibility,data showed that Surakarta Training Office in term of observingthe community aspiration was high. It showed, however, that theprocurement of box for accomodating communityâs suggestion andother means found were not sufficient. In this research alsoindicated that the human resources interm of the amount and theeducational level was already ideal for conducting the training.Research result also showed that the existing organizationalstructure has arranged the principal task and the function of eachdivision. It was also found that the existing means andinfrastructure, supporting tools for training were sufficient forsupporting the training process, eventhough they were far leftbehind comparing to the modern market job.Key words: training performance; productivity; responsibility